2015
DOI: 10.1080/15548627.2015.1100930
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal role of FOS-mediated BECN1/Beclin 1 upregulation in dopamine D2 and D3 receptor agonist-induced autophagy activation

Abstract: Autophagy dysfunction is implicated in the pathogenesis of Parkinson disease (PD). BECN1/Beclin 1 acts as a critical regulator of autophagy and other cellular processes; yet, little is known about the function and regulation of BECN1 in PD. In this study, we report that dopamine D2 and D3 receptor (DRD2 and DRD3) activation by pramipexole and quinpirole could enhance BECN1 transcription and promote autophagy activation in several cell lines, including PC12, MES23.5 and differentiated SH-SY5Y cells, and also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 65 publications
3
56
1
Order By: Relevance
“…to the CAB treatment (Gillam et al 2006, Wu et al 2016b, and the treatment of drug-resistant prolactinomas remains a challenging clinical problem. Accumulating evidence has proven that DAs, such as CAB, play a vital role in inducing autophagic cell death (Wang et al 2015. Wang et al (2015) reported that D2R/D3R agonist(s) might activate autophagy through the BECN1-dependent pathway and inhibit the tumor growth in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…to the CAB treatment (Gillam et al 2006, Wu et al 2016b, and the treatment of drug-resistant prolactinomas remains a challenging clinical problem. Accumulating evidence has proven that DAs, such as CAB, play a vital role in inducing autophagic cell death (Wang et al 2015. Wang et al (2015) reported that D2R/D3R agonist(s) might activate autophagy through the BECN1-dependent pathway and inhibit the tumor growth in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed that autophagy is evident after dopamine treatment for 6 h . The D 2 R and D 3 R agonists pramipexole (PPX) and quinpirole induce autophagy activation . Ammonia‐induced autophagy by mTOR‐inhibition is mediated by D 3 R .…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanism for the regulation of autophagy by dopamine is poorly studied. A recent study suggests that the increased Ca 2+ level may be involved in the autophagy induction, which is mediated by D 2 R and D 3 R . So far, there remains controversy over the role of Ca 2+ in modulating autophagy activity .…”
Section: Discussionmentioning
confidence: 99%
“…The sections were processed for the immunohistochemical detection of c‐Jun protein using a conventional avidin–biotin immunoperoxidase technique to localize an antiserum raised against a c‐Jun protein (rabbit polyclonal, Santa Cruz—catalog number: sc‐1694; ). Specificity of this antibody for c‐Jun as compared to other Jun family proteins has been recently evaluated (Yamazaki et al, ), as well as its ability to recognize c‐Jun from several species (Kurashige et al, ; Ogawa et al, ; Wang et al, ). Briefly, free‐floating sections were pretreated with hydrogen peroxidase for 10 min.…”
Section: Methodsmentioning
confidence: 99%